Steroid receptor coactivator TAIMAN is a new modulator of insect circadian clock - Smykal, Vlastimil; Chodakova, Lenka; Hejnikova, Marketa; Briedikova, Kristina; Wu, Bulah Chia-Hsiang; Vaneckova, Hana; Chen, Ping; Janovska, Anna; Kyjakova, Pavlina; Vacha, Martin; Dolezel, David (PLoS genetics, 2023)
TAIMAN (TAI), the only insect ortholog of mammalian Steroid Receptor Coactivators (SRCs), is a critical modulator of ecdysone and juvenile hormone (JH) signaling pathways, which govern insect development and reproduction. The modulatory effect is mediated by JH-dependent TAI's heterodimerization with JH receptor Methoprene-tolerant and association with the Ecdysone Receptor complex. Insect hormones regulate insect physiology and development in concert with abiotic cues, such as photo- and thermoperiod. Here we tested the effects of JH and ecdysone signaling on the circadian clock by a combination of microsurgical operations, application of hormones and hormone mimics, and gene knockdowns in the linden bug Pyrrhocoris apterus males. Silencing taiman by each of three non-overlapping double-strand RNA fragments dramatically slowed the free-running period (FRP) to 27-29 hours, contrasting to 24 hours in controls. To further corroborate TAIMAN's clock modulatory function in the insect circadian clock, we performed taiman knockdown in the cockroach Blattella germanica. Although Blattella and Pyrrhocoris lineages separated ~380 mya, B. germanica taiman silencing slowed the FRP by more than 2 hours, suggesting a conserved TAI clock function in (at least) some insect groups. Interestingly, the pace of the linden bug circadian clock was neither changed by blocking JH and ecdysone synthesis, by application of the hormones or their mimics nor by the knockdown of corresponding hormone receptors. Our results promote TAI as a new circadian clock modulator, a role described for the first time in insects. We speculate that TAI participation in the clock is congruent with the mammalian SRC-2 role in orchestrating metabolism and circadian rhythms, and that TAI/SRCs might be conserved components of the circadian clock in animals.
Keywords: Male; Ecdysone; cirkadiánní hodiny; Circadian Rhythm; Juvenile Hormones; Mammals; Cell Membrane; savci; cirkadiánní rytmus; Insecta; buněčná membrána; Circadian Clocks; mužské pohlaví; Animals; hmyz; juvenilní hormony; zvířata; ekdyson